Independent Prognostic Role of Postoperative Carcinoembryonic Antigen in Stage II Colon Cancer - Birsin, Zeliha; Aliyev, Vali; Jeral, Seda; Cebeci, Selin; Abbasov, Hamza; Demirci, Nebi Serkan; Alan, Özkan (Cerrahpaşa Medical Journal, 2025)
Objective: The aim was to evaluate the relationship between the G-8 geriatric screening score and clinical outcomes in elderly lung cancer patients treated with radiotherapy (RT) ± chemotherapy (CT). Methods: This retrospective study analyzed data from 80 lung cancer patients aged ≥65 years who underwent RT ± CT between 2010 and 2020. All patients were assessed using the G-8 screening tool. Survival analyses were performed using the Kaplan–Meier method, and toxicities were graded according to the Common Terminology Criteria for Adverse Events version 4. Prognostic factors for survival were evaluated using the log-rank test and Cox regression analysis. Results: The median age was 69 years, and 72.5% of patients had non–small cell lung cancer (NSCLC). The median progression-free survival (PFS) and overall survival (OS) were 11.5 and 17.5 months, respectively. Grade ≥3 toxicity occurred in 12.5% of patients, with higher rates among those with NSCLC and those receiving concurrent CT. Frail patients (92%, G-8 ≤14) showed no significant differences in survival or toxicity compared with non-frail patients (P = .652). While the conventional cutoff of 14 was not an independent prognostic factor for PFS or OS, a cutoff value of 10 was prognostic for PFS (P = .037) in the patient population. Conclusion: Most of the lung cancer patients aged ≥65 years were frail according to the G-8 score. The conventional cutoff of 14 did not correlate with treatment outcomes or toxicity; however, a cutoff value of 10 was prognostic for PFS. These findings highlight the need for improved assessment tools to better predict treatment-related toxicity and mortality in geriatric lung cancer patients. Cite this article as: Birsin Z, Aliyev V, Jeral S, et al. Independent prognostic role of postoperative carcinoembryonic antigen in stage II colon cancer. Cerrahpaşa Med J. 2025, 49, 0075, doi: 10.5152/cjm.2025.25075.